Latar Belakang Pemikiran Abu Hasan Asy’ari dan Abu Mansur al-Maturidzi Dalam Konsep Ahlussunnah Wal Jama’ah - Fathur Rohman. AR (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2021)
As a reaction to the deviant firqah, at the end of the 3rd century H, a group known as Ahlussunnah wal Jamaah arose, led by 2 great scholars in Usuluddin, namely Sheikh Abu Hassan Ali Al Asy'ari and Sheikh Abu Mansur Al Maturidi. The word Ahlussunnah wal Jamaah is sometimes referred to as Ahlussunnah only or Sunni only and sometimes referred to as Ash'ari or Asya'irah associated with the first great scholar, Abu Hassan Ali Ash'ari. Between Asy'ariyah and Maturidiyah themselves have several differences, among them are in the following matters: About the nature of God, about human actions, about the Qur'an, God's obligations, perpetrators of major sins, the appearance of God, and also God's promises. The differences that arise can be said only in the explanation of their teachings or in the matter of branches. If we examine the thoughts of al-Maturidi more closely, it will be found that al-Maturidi gave greater authority to the human mind than the Ash'ari. However, among the Maturidiah themselves, there are two groups that also have different tendencies of thought, namely the Samarkand group, namely the followers of al-Maturidi himself who understand his theology closer to the Mu'tazilah understanding and the Bukhara group, namely the followers of al-Bazdawi who are inclined to Asy'ariyah.